(3RgQ GdCce aj GdCeKGd hGdMces - (3GdMSf Hf eSYhO Hf eMeO, CHh Ydj, fhQ GdOjf GdjhSj,J (B1102 (3g` s
(3ChdgG (B:s
(3hHYO , aEf GdYde hCbhe MLg hGfLM eQYi hCHg i Mdg jJMdi HgG GdeJMdhf? hCQaY efUg jJLdi YfgG GdeJLdhf aEf GdYde ZPGA GdYbd s
(3BNQgG (B:s
(3hajg GdJhQjI HGdUHQ ef MjK Cfg Ydi eYfGg? hGfg GdeQ GdeYQha hCUdg UHQ Ke Naa HGdJScjf hGdJhQjI HGdYPQ ef MjK Cfg HeYfi GdEYJPGQ hgh Gdghi GdTOjO s
(3de jcf GdeDda hHBNQ UaMGJgG JYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B72 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeg (B- (3GdQHGW (B((3O(B191) s
Keywords: (3GdCOHs